Salivary Cortisol Levels in Patients with Oral Lichen Planus-A Pilot Case-Control Study - Ivana Skrinjar; Valentina Vidranski; Bozana Loncar Brzak; Danica Vidovic Juras; Ana Andabak Rogulj; Vlaho Brailo; Vanja Vucicevic Boras (MDPI AG, 2019)
It is known that cortisol level increases in stress situations. The aim of the study was to measure the levels of salivary cortisol in patients with oral lichen planus (OLP) and healthy controls. This was a case-control pilot study which included seven patients with reticular (non-symptomatic) OLP, eight patients with atrophic/erosive (symptomatic) OLP, and nine healthy controls. We hypothesized that patients with an atrophic/erosive type of OLP have higher levels of cortisol compared to patients with the reticular type of OLP and healthy controls. In each participant, unstimulated saliva was collected in order to determine cortisol levels by using commercially available ELISA kit. Our results have shown no differences between levels of salivary cortisol in OLP patients and healthy controls. We can conclude that further research with a larger number of OLP patients is needed to determine the correlation between OLP and stress.